2008
DOI: 10.1016/j.ajhg.2007.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Admixture Mapping of White Cell Count: Genetic Locus Responsible for Lower White Blood Cell Count in the Health ABC and Jackson Heart Studies

Abstract: White blood cell count (WBC) is an important clinical marker that varies among different ethnic groups. African Americans are known to have a lower WBC than European Americans. We surveyed the entire genome for loci underlying this difference in WBC by using admixture mapping. We analyzed data from African American participants in the Health, Aging, and Body Composition Study and the Jackson Heart Study. Participants of both studies were genotyped across >or= 1322 single nucleotide polymorphisms that were pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
151
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(165 citation statements)
references
References 36 publications
(38 reference statements)
13
151
0
1
Order By: Relevance
“…Lineage commitment of hematopoietic stem cells involves precise transcriptional and epigenetic regulation, creating the WBC traits in European ancestry populations 6 and less than 25% in African ancestry (AA) populations (in AA, a substantial proportion of the variation in WBC counts is attributed to a single variant-rs2814778-in DARC [Duffy Antigen Receptor for Chemokines (MIM: 613665)]). 3,13 In an effort to augment the discoveries from GWASs and to identify additional functional loci contributing to variation in WBC counts, we performed exome array-based meta-analysis of total and differential counts in a multiancestry samples from 25 studies.…”
Section: Introductionmentioning
confidence: 99%
“…Lineage commitment of hematopoietic stem cells involves precise transcriptional and epigenetic regulation, creating the WBC traits in European ancestry populations 6 and less than 25% in African ancestry (AA) populations (in AA, a substantial proportion of the variation in WBC counts is attributed to a single variant-rs2814778-in DARC [Duffy Antigen Receptor for Chemokines (MIM: 613665)]). 3,13 In an effort to augment the discoveries from GWASs and to identify additional functional loci contributing to variation in WBC counts, we performed exome array-based meta-analysis of total and differential counts in a multiancestry samples from 25 studies.…”
Section: Introductionmentioning
confidence: 99%
“…23 Research indicates that total WBC and neutrophil counts are lower among individuals of African descent because of the common African-derived ''null'' variant (rs2814778) of the Duffy antigen receptor for chemokines (DARC) gene. [24][25][26] It has been shown that by stopping the expression of DARC on RBCs, the Duffy null variant may alter the concentration and distribution of chemokines in the blood and tissue, [27][28][29][30] thus regulating neutrophil production and migration. This could be another reason for the low WBC counts among the apparently normal Malawian blood donors.…”
Section: Classification Of Severity Of Out-of-range Haematological Rementioning
confidence: 99%
“…First is the use of admixture mapping, tracing the location of particular SNPs associated with disease in populations of patients whose genomes are a mixture from at least two original populations, for example, African-Americans or Latinos (Price et al, 2007;Smith et al, 2004). Such an approach has already been used to map genes associated with several phenotypes whose frequency differs markedly between different population groups, including prostate cancer (Freedman et al, 2006), hypertension (Deo et al, 2007), skin pigmentation (McEvoy et al, 2006) and white blood cell count (Nalls et al, 2008).…”
Section: Variation In Populationsmentioning
confidence: 99%